Training and development of building surveyors in Malaysia - Ali, A.S.; Chen, J.W. (2012)
The Building Surveyor (BS) is a qualified person who performs Building Control works and other activities related to construction which involves an organised preparatory process of physical development, supervision of construction quality and Physical conditions of the building. BS plays a vital role in the building industry, especially in developed countries such as the United Kingdom and Australia. However, the awareness on the importance of BSs in Malaysia is still low. Most of the BS graduates work in various fields after they have graduated. The competencies and professional level of BS graduates has always been debated by other professionals in the building industry. Hence, the study concentrates on the academic training of BS programme in Malaysian Universities in order to determine the efficiency of the learning outcomes. Additionally, the paper also focuses on the employment trend of BS graduates in Malaysia. Triangulation approach was used in the study. From the results, it could be concluded that BS are still demanded in Malaysian building industry even without the Building Surveyor Act. In terms of training for BSs in universities, the programme structures from 3 major universities were found to have covered comprehensively the aspects of building construction, technology, maintenance and legal requirements.